2018
DOI: 10.1177/1937586718814822
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Signage Design: A Review on Recommendations for Effective Signing Systems

Abstract: This article provides a set of recommendations, selected from the systematic literature review carried out, regarding signage systems for healthcare institutions that can be used for designing or redesigning more competent signage systems. The signage systems in healthcare settings are usually poorly designed due to the expansion of the original facilities, a lack of awareness of existing guidelines by the developers, and a lack of agreement between the existing recommendations. There are several guidelines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…This environmental knowledge concerning potential routes and destination can be obtained from – amongst other resources – maps and information signage. Although signage is not the only wayfinding aid present in spatial settings, it has been proven of great importance in gathering environmental information and reducing wayfinding time and frustration (Carpman and Grant, 1993; Rodrigues et al., 2018). Multiple studies (Butler et al., 1993; Fewings, 2001) have suggested that signage carefully placed in the environment can reduce wayfinding difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…This environmental knowledge concerning potential routes and destination can be obtained from – amongst other resources – maps and information signage. Although signage is not the only wayfinding aid present in spatial settings, it has been proven of great importance in gathering environmental information and reducing wayfinding time and frustration (Carpman and Grant, 1993; Rodrigues et al., 2018). Multiple studies (Butler et al., 1993; Fewings, 2001) have suggested that signage carefully placed in the environment can reduce wayfinding difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Wall banners with text information are often found at the entrance to the hospital and are combined with wall (pictorial) direction signs on the walls in many places in the hospital (Rodrigues et al, 2019). Separate text banners can be found as confusing and the description of navigation could be inaccurate and simplified.…”
Section: Analysis Of Social Indirect Effects Of Selected Types Of Navigations In Hospitalsmentioning
confidence: 99%
“…Hospitals have been usually considered as stressful spaces. Evidence shows that a medical space with advanced design can reduce the patient’s and staff’s stress, increase the effectiveness of the medical care and, consequently, promote the general quality of medical services (Rodrigues et al , 2019). On the other hand, by the use of green spaces and landscape design techniques, this space can be improved in terms of performance and positively influence the physical and mental health of the patients and even their companions (Gupta, 2007; Marcus, 2000; Ulrich, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Beside them, the colours, labels, landmarks and signs must be used for wayfinding (Harper et al , 2019). The post-occupancy evaluation must be done regularly, and it would greatly help with revision of the hospital design elements such as the wayfinding (Rodrigues et al , 2019). The use of modern technologies, in addition to good space configuration, such as navigation applications and computerized modelling, can be much effective (Devlin, 2014).…”
Section: Introductionmentioning
confidence: 99%